Workplace Safety. Issue 4 (July 2021) - Simpson, Kathleen Rice
Abstract : Nurses should be free from sexual harassment and assault in the work place. There are many other types of harassment and discrimination that occur in the health care workplace. Nurses can be discriminated against and treated poorly for a number of reasons, including, but not limited to, race or ethnicity, age, gender, weight, socioeconomic status, level of education, years of experience, and mental health. We must do all that we can to role model supportive actions in the context of inappropriate behavior and to help make sure the workplace is safe for all nurses and other members of the health care team. A safe and healthy workplace for nurses promotes safe care for patients.